2014
DOI: 10.1021/ja508065e
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Reactivities of 2-Trityl- and 2-(Triphenylsilyl)pyrrolidine-Derived Enamines: Evidence for Negative Hyperconjugation with the Trityl Group

Abstract: X-ray structures of enamines and iminium ions derived from 2-tritylpyrrolidine (Maruoka catalyst) and 2-(triphenylsilyl)pyrrolidine (Bolm-Christmann-Strohmann catalyst) have been determined. Kinetic investigations showed that enamines derived from phenylacetaldehyde and pyrrolidine (R = H) or 2-(triphenylsilyl)pyrrolidine (R = SiPh3) have similar reactivities toward benzhydryl cations Ar2CH(+) (reference electrophiles), while the corresponding enamine derived from 2-tritylpyrrolidine (R = CPh3) is 26 times les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“… 13 Eqn (1) has already been used to successfully quantify the nucleophilicities of prolinol-based and MacMillan organocatalysts 14 as well as of enamines derived thereof. 15 As a consequence, the reactivity of the enamines studied in this work can straightforwardly be compared with relevant species that occur in many, more commonly used, enamine-activated reactions. 13 e ,15 Hence, a quantitative fundament for the understanding of both prebiotic relevance of ITO catalysts and their scope in organocatalytic reactions is provided in this work.…”
mentioning
confidence: 99%
“… 13 Eqn (1) has already been used to successfully quantify the nucleophilicities of prolinol-based and MacMillan organocatalysts 14 as well as of enamines derived thereof. 15 As a consequence, the reactivity of the enamines studied in this work can straightforwardly be compared with relevant species that occur in many, more commonly used, enamine-activated reactions. 13 e ,15 Hence, a quantitative fundament for the understanding of both prebiotic relevance of ITO catalysts and their scope in organocatalytic reactions is provided in this work.…”
mentioning
confidence: 99%
“…Negative hyperconjugation of the C(OSiMe 3 ) Ph 2 substituent was found to be responsible for the increased electrophilicity of the iminium ion derived from the HayashiJørgensen catalyst compared to the iminium ion derived from the unsubstituted pyrrolidine. 28 As substrates suitable for iminium activated reactions should be nucleophilic enough to react with iminium ions but not with the precursor carbonyl compounds, it was concluded that nucleophiles with 2<N<14 should be suitable substrates for iminium activated reactions. 27 Analogous analyses have also been performed for enamine-activated reactions.…”
Section: Nucleophilic Organocatalysismentioning
confidence: 99%
“…27 Analogous analyses have also been performed for enamine-activated reactions. 27,28 3.3. Why the reactivity selectivity principle cannot be a general rule Until the early 1970s decreasing selectivity with increasing reactivity was considered as a tenet of organic chemistry.…”
Section: Nucleophilic Organocatalysismentioning
confidence: 99%
“…Concerning the first successful preparation of enantiomerically-pure (S)-2-(triphenylsilyl)pyrrolidine [(S)-1], we established an indirect synthetic route via intermediate formation of 2-(methoxydiphenylsilyl)-N-Boc-pyrrolidine [1]. Recently, a detailed structural and kinetic investigation gave new insight into the structure-reactivity relation in enamines and iminium ions derived from 2-tritylpyrrolidine [7] and 2-(triphenylsilyl)pyrrolidine [8]. 4 ], which were obtained from the respective optically-pure chloride salts [1] by treatment with perchloric acid.…”
Section: Introductionmentioning
confidence: 99%